Long-term mutual phase locking of picosecond pulse pairs generated by a semiconductor nanowire laser - Mayer, B; Regler, A; Sterzl, S; Stettner, T; Koblmüller, G; Kaniber, M; Lingnau, B; Lüdge, K; Finley, J (Springer Nature, 2017)
The ability to generate phase-stabilized trains of ultrafast laser pulses by mode-locking underpins photonics research in fields, such as precision metrology and spectroscopy. However, the complexity of conventional mode-locked laser systems has hindered their realization at the nanoscale. Here we demonstrate that GaAs-AlGaAs nanowire lasers are capable of emitting pairs of phase-locked picosecond laser pulses with a repetition frequency up to 200 GHz when subject to incoherent pulsed optical excitation. By probing the two-pulse interference spectra, we show that pulse pairs remain mutually coherent over timescales extending to 30 ps, much longer than the emitted laser pulse duration (≤3 ps). Simulations performed by solving the optical Bloch equations produce good quantitative agreement with experiments, revealing how the phase information is stored in the gain medium close to transparency. Our results open the way to phase locking of nanowires integrated onto photonic circuits, optical injection locking and applications, such as on-chip Ramsey comb spectroscopy.